Encountering city governance: an analysis of street trading in Gaborone, Botswana - Lethugile, Goabamang (Department of Environmental and Geographical Science, 2020)
There is a need to review and recast how space is being planned and how regulations are responding to the realities of the informal economy. Street trading provides a critical platform to explore the dynamics and complexity of planning and management of informal activities in public spaces. This research explored how city governance shapes the practices of informal street trading in Gaborone, Botswana. It investigated how street traders navigate their daily trading and their spatial practices and strategies. Insights were gleaned through in-depth interviews with street traders in three different sites in Gaboroneand key informant interviews with politicians and government officials–both senior and lower level staff. Combining the government officials'and traders' perspectives has allowed for the exploration of the disjuncture betweenthe two. The interview findings indicated that the state continues to govern but with inappropriate tools, and traders continue to trade but in sub-optimum ways. The Gaborone Council has made some headway in accepting street traders but still provides little or no infrastructure. It is argued that traders themselves constitute public space, so their voices, practices, strategies and resilience need to be understood. The dissertation concludes by making recommendations that could improve conditions for all parties.